Konstytucyjność prawa jako podstawa demokratycznej kultury prawnej - Korycka-Zirk, Milena (Filozofia Publiczna i Edukacja Demokratyczna, 2013)
The notion of the constitutionalisation of law is the basis of analysis in modern democratic legal systems. The constitution influences the application of law and the constitutional method is the main approach that describes this process. The constitutionalisation of law should be understood in a broader sense as aspect of legal culture created in the process of interpretation of law reflected by the idea of constitution. The judicial review made by constitutional courts as in Kelsen’s conception or by common courts as in American model must be guided by the idea of maximalisation of human rights support as the element of democratic legal culture. This conception is compatible with the knowledge about constitutional norms and the way they are applied.